CLINICAL AND RADIOLOGICAL ASPECTS OF SUPERNUMERARY TEETH ON THE MIDLINE IN THE MIXED DENTITION - Dochioiu (Panainte); Sălceanu Mihaela; Cioloca Daniel; Adumitroaie Alina-Elena; Toma Vasilica (Romanian Dental Association for Education, 2021)
Supernumerary teeth represent isolated dental anomalies which may be present on the midline (mesiodens), in the premolar or molar region. Among the etiological factors are local factors, but they can also appear as manifestations of genetic syndromes. Familiarization with this anomaly is important for orthodontists, pedodontists and general dentists who frequently consult children at an early age. Supernumerary teeth can cause clinical complications. Early detection based on clinical and radiological examination and subsequent orthodontic and surgical interventions reduce the risk of occlusal disorders of the dental-maxillary apparatus.